(untitled) (PJDOL, 2023)
Provision of dynamic guidance services is an important aspect of any educational system of a country. Because of changes in the life style of people and working patterns in various sectors due to scientific and technological developments, several problems have also come up which are linked to various aspects of education, vocational training, social life, political system, health and well-being, religion-moral and spiritual values.